Communal narcissism and internet altruistic behavior of Chinese college student: A moderated mediating effect - Zimi Li; Xiangkui Zhang (PLoS ONE, 2026)
This research aimed to examine the relations among communal narcissism, Internet impression management, self-esteem and Internet altruistic behavior. This study measured 700 university students from 3 universities in the Northeast using the Narcissistic Personality Inventory, the Internet Impression Management Scale, the Self-Esteem Scale, and the Internet altruistic Behavior Scale, with 675 effective participants. The results of the study showed that the direct effect of communal narcissism on university students’ Internet altruistic behavior was significant. After adding Internet impression management as a mediating variable, the effect of communal narcissism on university students’ online prosocial behavior remained significant. At the same time, self-esteem played a moderating role in the relationship between communal narcissism and Internet impression management.